2017
DOI: 10.1186/s12876-017-0599-4
|View full text |Cite
|
Sign up to set email alerts
|

How to select patients and timing for rectal indomethacin to prevent post-ERCP pancreatitis: a systematic review and meta-analysis

Abstract: BackgroundAcute pancreatitis is a severe complication of endoscopic retrograde cholangiopancreatography (ERCP). Previous meta-analyses have shown that indomethacin effectively prevents this complication; however, the data are limited. We performed a systematic review and meta-analysis to clarify the applications for rectal indomethacin.MethodsA systematic search was performed in June 2016. Human prospective, randomized, placebo-controlled trials that compared rectally administered indomethacin with a placebo f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0
2

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 31 publications
2
15
0
2
Order By: Relevance
“…Wan et al . showed that preoperative administration of indomethacin was better than postoperative administration [ 47 ], but in this study, the authors combined the intraoperative administration of Levenick et al and postoperative administration [ 15 ]. The studies of Inamdar et al and Sethi et al showed no difference between the preoperative and postoperative groups [ 45 , 46 ], but the above studies included eight and seven studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Wan et al . showed that preoperative administration of indomethacin was better than postoperative administration [ 47 ], but in this study, the authors combined the intraoperative administration of Levenick et al and postoperative administration [ 15 ]. The studies of Inamdar et al and Sethi et al showed no difference between the preoperative and postoperative groups [ 45 , 46 ], but the above studies included eight and seven studies, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have evaluated the preventive effects of rectal indomethacin or diclofenac in post-ERCP pancreatitis, with a meta-analysis con rming their protective effect 11 . Another meta-analysis showed that rectal indomethacin administration prior to ERCP is effective for the prevention of post-ERCP pancreatitis in high-risk patients 12 . Phospholipase A2 activity is inhibited by rectal NSAIDs in acute pancreatitis, possibly regulating proin ammatory mediators.…”
Section: Discussionmentioning
confidence: 99%
“…A recently published meta-analysis of 4741 patients from 17 prospective trials showed that rectally administered diclofenac or indomethacin before, or closely after, ERCP were safe and effective in the prevention of PEP in all patients [ 24 ]. Based on pharmacokinetics, the peak plasma concentration of indomethacin and complete bioavailability can be reached 30 min after the rectal administration of indomethacin and the superior effect of its administration before ERCP was confirmed in high-risk patients [ 20 , 25 ]. Thus, our study preferred the strategy of pre-procedural administration.…”
Section: Discussionmentioning
confidence: 99%